The Non-Parametric Identification of the Mixed Proportional Hazards Competing Risks Model - Jaap H. Abbring; Gerard J. van den Berg (Tinbergen Institute, 2000)
We prove identification of dependent competing risks models in which each risk has a mixed proportional hazard specification with regressors, and the risks are dependent by way of the unobserved heterogeneity, or frailty, components. We show that the conditions for non-parametric identification given by Heckman and Honoré(1989) can be relaxed. We generalize the results for the case in which multiple spells are observed for each subject.
Keywords: 330; competing risks; mixed proportional hazard; non-parametric identification; frailty; duration model; multiple spells; Kausalanalyse; Multivariate Analyse; Dauer; Risiko; Theorie